Effect of pasteurization of shell egg on its quality characteristics under ambient storage - Shenga, E. (Springer-Verlag, 2010)
Three thermal processes viz. dry (55°C, 2 h), moist (57°C, 5 min) and microwave (power 9, 20 sec) were studied to determine their efficacy for the pasteurization of intact chicken eggs based on the extent of inactivation of artificially inoculated Salmonella typhimurium (ST) in the yolk of shell eggs and alteration in albumen protein solubility (APS). Moist heat treatment was superior to others as it brought about 2 log cfu/ml reduction of inoculated ST in much less time than dry heating but changes in APS were not significant. Subsequent quality evaluation of normal (uninoculated) eggs subjected to moist heat pasteurization during 15 days of ambient (35°C, 36% RH) (35 ± 0.5°C, 36 ± 2% RH)storage revealed no significant effect on percent loss in egg weight, albumen pH, viscosity of albumen and yolk and thiobarbituric acid values between pasteurized and unpasteurized eggs. Pasteurization had no adverse effect on foam volume and foam stability of albumen during storage in comparison to those of raw eggs. Naturally occurring aerobic mesophilic bacteria, coliforms, staphylococci, yeast and moulds on the egg shell surface and in egg contents got markedly reduced by pasteurization of shell eggs and their multiplication also retarded during storage. Both pasteurized and raw eggs remained fairly acceptable sensorily up to 10 days of storage at ambient conditions.